2020
DOI: 10.1111/obr.13010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and effectively addressing disparities in obesity: A systematic review of the psychological determinants of emotional eating behaviours among Black women

Abstract: Emotional eating may be a particularly important contributor to differences in body weight and weight loss response to behavioural interventions among non-Hispanic Black women. We performed a systematic review on the impact of psychological factors (stress, anxiety, depression, and discrimination) upon emotional eating and weight among non-Hispanic Black women, applying the Preferred Reporting Items for Systematic Reviews and Meta-analysis for relevant studies. The initial search yielded 4593 articles with 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 74 publications
(138 reference statements)
1
15
0
Order By: Relevance
“…Black men and women who report experiencing racial discrimination have higher BMI [33,[36][37][38], and discrimination predicts the incidence of obesity and weight gain in Black women [32]. Experiencing discrimination can also have implications for obesity-related behaviors [34,35,[39][40][41]. Studies show that discrimination is associated with obesogenic dietary behaviors among Black women and men [34,35,39,42], and worry about discrimination or racial vigilance has been cited as a barrier to physical activity among Black men [41].…”
Section: Racism and Obesitymentioning
confidence: 99%
“…Black men and women who report experiencing racial discrimination have higher BMI [33,[36][37][38], and discrimination predicts the incidence of obesity and weight gain in Black women [32]. Experiencing discrimination can also have implications for obesity-related behaviors [34,35,[39][40][41]. Studies show that discrimination is associated with obesogenic dietary behaviors among Black women and men [34,35,39,42], and worry about discrimination or racial vigilance has been cited as a barrier to physical activity among Black men [41].…”
Section: Racism and Obesitymentioning
confidence: 99%
“…It has been recognized that the processes which mediate the relationship between ELA and adult obesity might differ between men and women [110][111][112]. For example, a recent systematic review found that perceived stress from structural racism and weight stigma among black women creates negative emotions which predict emotional eating [113]. These stressors may then increase metabolic disturbance.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…Food consumption represents food and nutrients intake per se and eating behavior involves the psychological and cultural aspects of eating and its practices 12 . Several studies have demonstrated an association between racial discrimination experiences throughout life and poor eating habits in the last decade 4,[13][14][15] . In 2020, a systematic review of the impact of psychological factors (stress, anxiety, depression, and discrimination) on emotional eating and weight among American Black women suggested that negatively perceived stress may be predictive of emotional eating 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated an association between racial discrimination experiences throughout life and poor eating habits in the last decade 4,[13][14][15] . In 2020, a systematic review of the impact of psychological factors (stress, anxiety, depression, and discrimination) on emotional eating and weight among American Black women suggested that negatively perceived stress may be predictive of emotional eating 15 . As a recent manuscript published in the American Journal of Clinical Nutritional recommended, researchers should consider more seriously the impact of race and the effects of racism and racial discrimination in nutritional outcomes.…”
Section: Introductionmentioning
confidence: 99%